Looking into a crystal ball: printing and patterning self-assembled peptide nanostructures. Issue 42 (21st October 2022) - Alves, Wendel A.; King, Gavin M.; Guha, Suchismita
Abstract : Recent advances in printing and patterning self-assembled peptide nanostructures are highlighted. Ice lithography, which thus far has not been applied to biological macromolecules, is promising for functionalizing and patterning peptides. Abstract : The solution processability of organic semiconductors and conjugated polymers along with the advent of nanomaterials as conducting inks have revolutionized next-generation flexible consumer electronics. Another equally important class of nanomaterials, self-assembled peptides, heralded as next-generation materials for bioelectronics, have a lot of potential in printed technology. In this minireview, we address the self-assembly process in dipeptides, their application in electronics, and recent progress in three-dimensional printing. The prospect of a generalizable path for nanopatterning self-assembled peptides using ice lithography and its challenges are further discussed.